PEMAKNAAN LINGGA-YONI DALAM MASYARAKAT JAWA-HINDU DI KABUPATEN BANYUWANGI PROVINSI JAWA TIMUR: STUDI ETNOARKEOLOGI - Wibowo, Bayu Ari (Humanis, 2016)
Archaeological relics in Banyuwangi are very diverse ranging from artifacts, sites, and locus and can be classified into regional cultural heritage which is tangible. The artifacts can be sacred or profane. Archaeological relic which served as the research object of this thesis is a lingga-yoni. Hinduism sees a lingga-yoni as an ultimate embodiment of truth or ultimate embodiment of beauty and at the same time a depiction of religious and philosophical truth in the form of an icon. The icon has a certain form, which as a whole or part by part is representing certain meanings. The aim of this study is to reveal the variety of forms of lingga-yoni exists in Banyuwangi and the meaning of lingga-yoni in Javanese-Hinduism society in Banyuwangi. The research used several data collection and data analysis methods, to reveal the problem of the research. The methods being used in this research were covering the stages of data collection, i.e. by way of observation, interview, and literature study. The next stage was data processing by way of qualitative analysis, ethno-archaeological, and artifactual analysis. The result of research shows that lingga-yoni which exists in Banyuwangi Regency generally has half oval, oval, pseudo, cylindrical, and ractangular forms. Lingga-yoni by Javanese-Hinduism society is understood as a symbolization of Sang Hyang Widhi which is manifested as Siwa Sakti, the ancestor, and Dhanyang, thereby they can feel close with Him and always making contact through meditation or by meditating.
Keywords: Lingga-Yoni, Javanese-Hinduism, Ethno-archaelogical